N-Glycosylation in piroplasmids: diversity within simplicity - Florin Christensen, Mónica (2021)
N-glycosylation has remained mostly unexplored in Piroplasmida, an order of tick-transmitted pathogens of veterinary and medical relevance. Analysis of 11 piroplasmid genomes revealed three distinct scenarios regarding N-glycosylation: Babesia sensu stricto (s.s.) species add one or two N-acetylglucosamine (NAcGlc) molecules to proteins; Theileria equi and Cytauxzoon felis add (NAcGlc)2-mannose, while B. microti and Theileria s.s. synthesize dolichol-P-P-NAcGlc and dolichol-P-P-(NAcGlc)2 without subsequent transfer to proteins. All piroplasmids possess the gene complement needed for the synthesis of the N-glycosylation substrates, dolichol-P and sugar nucleotides. The oligosaccharyl transferase of Babesia species, T. equi and C. felis, is predicted to be composed of only two subunits, STT3 and Ost1. Occurrence of short N-glycans in B. bovis merozoites was experimentally demonstrated by fluorescence microscopy using a NAcGlc-specific lectin. In vitro growth of B. bovis was significantly impaired by tunicamycin, an inhibitor of N-glycosylation, indicating a relevant role for N-glycosylation in this pathogen. Finally, genes coding for N-glycosylation enzymes and substrate biosynthesis are transcribed in B. bovis blood and tick stages, suggesting that this pathway is biologically relevant throughout the parasite life cycle. Elucidation of the role/s exerted by N-glycans will increase our understanding of these successful parasites, for which improved control measures are needed.